Innate (and Innate-like) Lymphoid Cells: Emerging Immune Subsets With Multiple Roles Along Transplant Life. Issue 12 (December 2021) - Charmetant, Xavier; Bachelet, Thomas; Déchanet-Merville, Julie; Walzer, Thierry; Thaunat, Olivier
Abstract : Transplant immunology is currently largely focused on conventional adaptive immunity, particularly T and B lymphocytes, which have long been considered as the only cells capable of allorecognition. In this vision, except for the initial phase of ischemia/reperfusion, during which the role of innate immune effectors is well established, the latter are largely considered as "passive" players, recruited secondarily to amplify graft destruction processes during rejection. Challenging this prevalent dogma, the recent progresses in basic immunology have unraveled the complexity of the innate immune system and identified different subsets of innate (and innate-like) lymphoid cells. As most of these cells are tissue-resident, they are overrepresented among passenger leukocytes. Beyond their role in ischemia/reperfusion, some of these subsets have been shown to be capable of allorecognition and/or of regulating alloreactive adaptive responses, suggesting that these emerging immune players are actively involved in most of the life phases of the grafts and their recipients. Drawing upon the inventory of the literature, this review synthesizes the current state of knowledge of the role of the different innate (and innate-like) lymphoid cell subsets during ischemia/reperfusion, allorecognition, and graft rejection. How these subsets also contribute to graft tolerance and the protection of chronically immunosuppressed patients against infectious and cancerous complications is also examined. Abstract : Supplemental Digital Content is available in the text.